Variations of Lipoprotein(a) Levels in the Metabolic Syndrome: A Report from the Maracaibo City Metabolic Syndrome Prevalence Study - Valmore Bermúdez; Joselyn Rojas; Juan Salazar; Luis Bello; Roberto Áñez; Alexandra Toledo; Maricarmen Chacín; Miguel Aguirre; Marjorie Villalobos; Mervin Chávez; María Sofía Martínez; Wheeler Torres; et al. (Journal of Diabetes Research)
Background. Lipoprotein(a) [Lp(a)] is a known risk factor for cardiovascular disease, yet its influence on metabolic syndrome (MS) is still controversial. The purpose of this study was to assess the impact generated by this diagnosis in serum Lp(a) concentrations. Materials and Methods. A total of 1807 subjects of both genders (55.3% women and 44.7% men) belonging to the Maracaibo City Metabolic Syndrome Prevalence Study were evaluated. Results were expressed as Mean ± SD, determining differences through Student’s t-test and One-Way ANOVA test. Multiple logistic regression models were utilized for analyzing factors associated with elevated serum Lp(a) levels and MS. Total cholesterol and LDL-C were corrected according to Lp(a)-Cholesterol when necessary. Results. No differences were found in Lp(a) values between genders; P=0,292. The association between MS and the classification of Lp(a) was statistically significant (χ2=28.33; P<0,0001), with greater levels in subjects with this diagnosis. In the univariate analysis, subjects with each of the separate diagnostic criteria showed higher serum Lp(a) concentrations, except for hyperglycemia. Conclusions. Lp(a) values exhibit important variations regarding MS and each of its components. Impaired fasting glucose appeared as a protecting factor against elevated Lp(a) concentrations, whereas its association with LDL-C and hs-CRP suggests a potential pro-inflammatory role.